Síndrome de disfunción cognitiva del perro como modelo de investigación de las enfermedades neurodegenerativas del humano - Gallego, Diana Y.; Figueroa, Judith; Orozco, Camilo A. (Revista de la Facultad de Medicina, 2010)
In humans and canines, the aging process increases the risk of neurodegenerative diseases such as Alzheimer's disease and cognitive dysfunction syndrome in senior dogs. These pathological changes in different brain areas cause dementia syndromes, generating an apparent cognitive deficit characterized by behavioral changes such as alterations in memory and learning processes. The deleterious effects on quality of life in human patient affected by AD, promote the need to find similar pathologies affecting other species, making these, experimental models useful for the investigation of human suffering. Recently it has been suggested a close similarity between several of the clinical, anatomical and physiological characteristic of the Alzheimer's disease and the cognitive dysfunction syndrome senior dogs, which includes the formation and accumulation of amyloid plaques, apoptosis of cholinergic neurons with a consequent reduction of the neurotransmitter acetyl - hill, progressive type cognitive deficits and alterations in the sleep-wake cycle, among others. Thus, progress in understanding the processes involved in the pathophysiology of cognitive dysfunction syndrome senior dogs, and recognizing their similarities to those that occurred during the Alzheimer's disease, has facilitated studies aimed at understanding some aspects that have not been well detailed neurodegenrativas disease in humans. Moreover, considering the high probability of getting the cognitive dysfunction syndrome senior dogs, which is identified in several canine populations, allows for the possibility of proposing the dog changes, as an optimal model for research experimentate neurodegenerative processes associated with aging in humans.